An Assessment of Factors that Influence Takaful Patronage in Kano Metropolis - Yahya, Muhammad Ghiyath; Muhammad, Aliyu Dahiru; Abdullahi, Muhammad Ibrahim; Sanusi, Soliha (Journal of Accounting Research, Organization and Economics, 2025)
Objective Takaful holds significant promise in Nigeria, particularly in the Northern region, which is predominantly inhabited by Muslims. Additionally, it is anticipated that the Northern region, which is predominantly Muslim, will favor Takaful due to the lack of interest in conventional insurance. Thus, the main objective of this study is to empirically examine the factors that influence patronage of Takaful among senior secondary school teachers in Kano metropolis.Design/Methodology This study adopted a descriptive survey research design. The study used primary data, and a questionnaire served as an instrument for data collection. The study employed a random sampling technique in selecting secondary schools from each of the eight metropolitan local governments in Kano state, and a purposive sampling technique was adopted to capture the target respondents. The study employed Structural Equation Modelling (SEM) by using SPSS version 22 and AMOS statistical software.Results The findings of the study reveal that all the independent variables of the study, namely awareness, attitude, subjective norm and perceived behavioral control, were found to significantly influence patronage of Takaful.Research limitations/implications Therefore, the study recommendations are; Firstly, National Insurance Commission (NAICOM) to liaise with relevant stakeholders (i.e., Takaful Companies) and come up with effective promotion strategy i.e., through the use of both online and offline media in order to improve the awareness level. Secondly, NAICOM and takaful companies to develop a blue print that will aim at improving the attitude of Senior Secondary School Teachers in Kano toward takaful products and services through organizing series of workshops, symposium and seminars. Thirdly, Takaful companies in collaboration with Kano State Secondary Schools Management Board (KSSSMB) to embark on enlighten Senior Secondary School Teachers in Kano to purchase takaful products and services. Lastly, Takaful companies in Kano, KSSSMB as well as relevant stake holders to advocate for incorporating Takaful into insurance policy as alternative to conventional insurance because of its recognition as an ethical mechanism for risk management.Novelty/Originality The research is novel as it highlights the relevant of takaful at school level, an area largely ignored.